Upaya Meningkatkan Hasil Belajar IPA Melalui Model Pembelajaran Kooperatif Tipe Jigsaw pada Siswa Kelas IV SD Negeri 193 Palembang - Fauziah Fauziah (Departement of Mathematics Education, 2022)
This study used action research (classroom action research) in two rounds. Each round consists of four stages, namely: design, activity and observation, reflection, and revision. The formulation of the problem in this study is: Can the use of the Jigsaw type cooperative learning model improve science learning outcomes for fourth grade students at SD Negeri 193 Palembang? The purpose of this action research was to find out the increase in science learning outcomes for fourth grade students at SD Negeri 193 Palembang through the application of a jigsaw cooperative learning model. The subjects in this study were fourth grade students at SD Negeri 193 Palembang, totaling 26 students. The data obtained is in the form of formative test results, observation sheets of teaching and learning activities. From the results of data analysis, it can be seen that learning using the Jigsaw model has a positive impact on improving science learning outcomes for fourth grade students at SD Negeri 193 Palembang. The increase in learning outcomes obtained by these students can be seen starting from before using the jigsaw cooperative learning model, namely the percentage of learning completeness starting from the pre-cycle of 46.15%, Cycle I 73.08% and then increasing in cycle II of 88.46%. Based on the results of the data analysis, the research was considered good and successful because classical learning mastery had reached >85%. Based on the results obtained in this study, it can be concluded that the use of the jigsaw type cooperative learning model in Civics learning can increase the activity and learning outcomes of fourth grade students at SD Negeri 193 Palembang.